Avaliação micromecânica de agregados graúdos sujeitos àreação álcali agregado - RAA - Costa, Ricardo Vasconcelos Gomes da (2019)
Despite being one of the most used materials in the world, concrete may present certain limitations, especially with regard to durability aspects. In its constitution, aggregates have an important function in performance characteristics and in durability and lifespan. Classical pathologies can affect the material by reducing service life or requiring maintenance and corrections prior to the expected project time. One pathology that has attracted the attention of the scientific community is the Alkali-Aggregate Reaction (AAR). This is an expansive reaction resulting from the interaction between alkalis (present in cement and aggregates) and specific silica species (also present in the aggregate). The standards recommends limits on the standards and total quantities of alkalis per cubic meter of concrete and quantity of alkalis in the Portland cement. Based on the above, it is important to considerer the potential susceptibility of the aggregates through expansive mechanisms. The objective of the present work is to evaluate the aggregates subjected to the Aggregate Alkaline Reaction (RAA), using micromechanical and non destructive techniques, in order to analyze if the rock hardness (large aggregate) as well as its fracture toughness influence the process of RAA, still try to correlate their chemical characteristics with the pattern of hardness and crack propagation. For this, 65 samples of commercially available rocks were collected in the Northeast region of Brazil. With them, we performed tests to evaluate elemental composition and crystalline phases using X-ray fluorescence (FRX) and X-ray diffraction (XRD) techniques. After that, 05 samples were chosen to evaluate the hardness (HV) and fracture toughness (K1C) standards, using nondestructive ultrasonic test and Vickers Microhardness (indentation method). The correlation between the results to be obtained in the study of the microstructural and micromechanical properties of the aggregates will be studied. Then, the influence models of the variables in the studied properties will be analyzed statistically, thus seeking the validation and coherence of the obtained data. Subsequently, surfaces of responses will be elaborated to better visualize the chemical and mineralogical influence of the aggregate to the formation of RAA, and also on its micromechanical properties (Hv and K1C), being evaluated the possible interactions seeking results. The studies will be carried out with the aid of DIFFRAC.TOPAS software (for Rietveld refinement) and MAZE (for colorization of the phases, by SEM image)